Nurses’ Perceptions of Pressure Ulcer Risk and Prevention Practices in the Intensive Care Unit, Makassar - Zaenal Zaenal; Rini Mustamin (PT. Anagata Sembagi Education, 2026)
Pressure ulcers remain one of the most serious complications among critically ill patients in the Intensive Care Unit (ICU), serving as a key indicator of healthcare quality and patient safety. This study aims to analyze the influence of nurses’ perceptions of pressure ulcer risk on their prevention practices in the ICU of Makassar City General Hospital. A quantitative approach with a correlational observational and cross-sectional design was employed. Primary data were obtained through structured questionnaires assessing risk perception and observation sheets evaluating prevention practices, while secondary data were collected from hospital documents related to policies and pressure ulcer incidence reports. The findings revealed that most nurses had a good perception of pressure ulcer risk and demonstrated adequate prevention practices, with a significant relationship between perception and preventive performance. The results indicate that a higher perception of risk enhances adherence to evidence-based preventive actions such as patient repositioning, skin integrity monitoring, and the use of pressure-relieving devices. Theoretically, this study reinforces the application of the Health Belief Model in critical nursing practice, emphasizing that individual perception plays a crucial role in shaping preventive behavior. Practically, the study provides empirical evidence to support the development of training programs and quality improvement policies focused on strengthening nurses’ risk perception of pressure ulcers as part of patient safety strategies in hospitals